Tribunal for consumer claims in Malaysia: a review on the protection for consumers / Nur Safuraa Shamshuddin … [et al.] - Shamshuddin, Nur Safuraa; Mohd Izhari, Siti Rakna Syafidah; Mior Muhamad Sharudin, Nura Ashikin; Abdul Rahim, Noor Nadiatul Akmar (Faculty of Law, 2009)
The objective of this research is to study the role and functions of the Tribunal for Consumer Claims. This research provides an overview on Tribunal in Malaysia, the law that governs the Tribunal which is the Consumer Protection Act 1999. The Tribunal established under the section 85, Part XII of the Consumer Protection Act 1999 which took effect on 15 October 1999. The Tribunal is different from the civil court, where the Tribunal does not permitted the parties to be represented by any legal personnel and its limitation. Here, the historical background is briefly discussed and the current position of consumer protection law after the amendment of the Act. Furthermore, this research covered the legal administration of the Tribunal. This research had analyzed the effectiveness of the Tribunal based on all information and data gathered. Apart from that, this research identifies the effectiveness based on the commentaries on the Act itself. After identifying whether the Tribunal has achieved its goal in protecting the consumers' right, this research has provided some recommendations for the improvement of the Tribunal in future.